Service Quality of Bus Performance in Asia: A Systematic Literature Review and Conceptual Framework - Bakar M.F.A.; Norhisham S.; Katman H.Y.; Fai C.M.; Azlan N.N.I.M.; Samsudin N.S.S. (MDPI, 2023)
conceptual framework; literature review; public transport; service quality; transportation policy; transportation system; urban transport; Asia